Prevalence of Borrelia burgdorferi sensu lato genospecies in host-seeking Ixodes ricinus ticks in selected South Bohemian locations (Czech Republic) - Danielová, V; Daniel, M; Rudenko, N; Golovchenko, M (Central European journal of public health, 2004)
In selected localities of Ceské Budĕjovice and Ceský, Krumlov districts, well known by stable high incidence of tick-borne encephalitis (TBE) human cases but with low incidence of Lyme borreliosis, monitoring of Borrelia burgdorferi sensu lato (s.l.) in Ixodes ricinus ticks was performed. Research was also aimed at the spread of I. ricinus to mountain areas of this region (National Park Sumava), as well as at investigating this tick for B. burgdorferi s.l. genospecies and TBE virus infection. Altogether 498 nymphs, 88 females and 11 males of I. ricinus from lower locations and 58 nymphs from mountain locations (760-1080 m above sea level) were tested by polymerase chain reaction. In lower locations total prevalence of Borrelia burgdorferi s.l. in Ixodes ricinus ticks was 35%. Single infection of Borrelia afzelii, B. garinii and B. burgdorferi sensu stricto (s.s.) was found in 59, 50 and 63 ticks, respectively (i.e. in 12.8, 11.2 and 14.1%). Double infection was found in 42 ticks (6.0%) and triple infection in three ticks (0.4%). The high frequency of B. burgdorferi s.s. exceeds the as yet reported occurrence in Central Europe. These circumstances are discussed. In mountain locations B. afzelii was found in five ticks, that including two co-infection with B. garinii, in elevations of 762 m and 1024 m above sea level, respectively. This fact signals a real danger of human infections in a region that was previously deemed to be without risk. Moreover, this region is more and more the target destination of tourist activities. The results also suggest that the penetration of infection can be rapid and formation and establishment of natural focus of Lyme borreliosis might be rather quick.
Keywords: viry klíšťové encefalitidy; Polymerase Chain Reaction; Česká republika; zvířata; monitorování životního prostředí; zeměpis; arachnida jako vektory; polymerázová řetězová reakce; Encephalitis Viruses, Tick-Borne; Animals; lidé; Epidemiological Monitoring; Geography; Czech Republic; Environmental Monitoring; epidemiologické monitorování; nymfa; Arachnid Vectors; techniky amplifikace nukleových kyselin; Nymph; Female; Ticks; klíště; Ixodes; Borrelia burgdorferi; Male; ženské pohlaví; Nucleic Acid Amplification Techniques; Humans; mužské pohlaví; prevalence; klíšťata; Prevalence